100-th AES Convention in Copenhagen - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1996)
Audio Engineering Society Conventions are organized regularly on a worldwide scale twice a year. The Spring Conventions in Europe are detoned with subsequent even numbers, while the Fall Conventions in America - with odd ones. All AES Conventions, apart from other more specialized meetings, such as e.g. AES Conferences, separately numbered, bear a specified character. They are, first of all, organizational meetings of the AES-Board of Governors with the Region- and Section-Officers, and Members of numerous AES Committees, as well of the Headquarters and Regional Offices. All members comming from various countries work together intensively during the Convention days, taking advent age of the direct personal contacts and opportunity for discussion.